On the edge of the eurasian steppes: the sarmatian culture in the 1st–3rd centuries ad east of the Carpathians - Grumeza Lavinia; Cojocaru Victor (Поволжская археология)
The paper analyses the Sarmatian culture east of the Carpathians during the 1st-3rd centuries AD, shedding light on their burial practices, artefacts, and socio-economic interactions. The term ‘Sarmatians’ encompasses several nomadic groups with common genetic, linguistic or territorial ties, including the Iazyges, Roxolani, Alans, Siraces and Aorsi. Archaeological evidence indicates significant cultural changes during the Middle and at the beginning of Late Sarmatian periods, marked by rich burials, imported goods and weapons. The study focuses on necropolises, which reveal burial patterns, grave goods, and anthropological insights such as intentional cranial modification. Notable grave goods include beads, mirrors and swords, reflecting the social status and cultural connections of the Sarmatian elite. Trade networks facilitated the exchange of horses for luxury goods, highlighting the economic importance of the Sarmatians in Eurasia. Despite their interactions with neighbouring regions, the Sarmatians maintained a conservative cultural identity distinct from Roman influence. This research highlights the complexity of Sarmatian society and its enduring legacy between the Carpathians and the Prut River.